1997
DOI: 10.1021/bk-1997-0671.ch018
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic Hydrocarbons, Linear Alkylbenzenes, and Highly Branched Isoprenoids in Molluscs of the Adriatic Sea, Italy

Abstract: Aliphatic hydrocarbons and linear alkylbenzenes (LABs) were determined in four species of molluscs of the Central Adriatic Sea: two bivalves, Mytilus galloprovincialis, Solen vagina and two gastropods, Patella vulgata, Cassidaria echinophora. The concentrations of total aliphatic hydrocarbons determined in the mollusc samples were between 35.0 and 68.1 μg g -1 dry wt, and they may be considered within normal limits for areas reported to be mildly polluted. In P. vulgata and in C. echinophora over 70% and 50%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…LABs are persistent in the environment (Takada and Ishiwatari 1990), hydrophobic (Sherblom et al 1992) and, therefore, can be accumulated in sediments and biological tissues. Although there are many reports on LABs in sediment and biological samples from developed countries (Albaigés et al 1987;Sherblom and Eganhouse 1991;Bouloubassi and Saliot 1993;Hong et al 1995;Serrazanetti et al 1997;Phillips et al 2001 andreferences in Takada andEganhouse 1998), only our report is available from this region .…”
Section: Introductionmentioning
confidence: 89%
“…LABs are persistent in the environment (Takada and Ishiwatari 1990), hydrophobic (Sherblom et al 1992) and, therefore, can be accumulated in sediments and biological tissues. Although there are many reports on LABs in sediment and biological samples from developed countries (Albaigés et al 1987;Sherblom and Eganhouse 1991;Bouloubassi and Saliot 1993;Hong et al 1995;Serrazanetti et al 1997;Phillips et al 2001 andreferences in Takada andEganhouse 1998), only our report is available from this region .…”
Section: Introductionmentioning
confidence: 89%
“…However, recent studies by Heilprin et al (unpublished data) have shown that white croaker near the OCSD outfall feed extensively on larvae of a drain fly (Clogmia albipunctatus) that breed in the wastewater treatment facility and are discharged to the ocean with the effluent. Serrazenetti et al [16] also observed differences among four species of mollusk in tissue LAB concentrations related to feeding habits, with the highest concentrations in detritivores and the lowest in herbivores. Pacific sanddab and chub mackerel are considered to be generalist feeders that consume planktonic crustaceans and small fish, whereas California scorpionfish eat small crabs, shrimps, and fish [34].…”
Section: Discussionmentioning
confidence: 93%
“…Consequently, the relatively higher LAB concentrations in white croaker from the near-outfall station are consistent with the presumed differences in diets, although this may reflect direct ingestion of effluent particles (e.g., fly larvae) rather than benthic-pelagic coupling. Serrazenetti et al [16] also observed differences among four species of mollusk in tissue LAB concentrations related to feeding habits, with the highest concentrations in detritivores and the lowest in herbivores.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations